2015
DOI: 10.3390/buildings5010056
|View full text |Cite
|
Sign up to set email alerts
|

Building to Net Zero in the Developing World

Abstract: This paper discusses the design of a zero energy home in Panama. The standards for zero site energy as well as other performance factors are used as the basis for the analysis. A description of the construction type, energy use, active and renewable systems, and other features of this particular zero energy building are provided to facilitate a better understanding of efficient and sustainable residential design for hot-humid climates. This understanding is critical to facilitating net zero energy building dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Moreover, in Argentina, under the same Cfa climate, the same original U-value was encountered for reaching nZEB [35] for different building types, but to achieve NZEB the improved case presented U-values lower than the original [28] (Table 3). On the other hand, to achieve NZEB, the improved U-values differed significantly in studies based in countries with an Af climate, such as Brazil [39] and Panama [54] (Table 3), despite the same type of building being analyzed (Table 1). An agreement is encountered under the same type of climate, Aw [43,55], for the improved U-values in walls and windows, despite different building types, to achieve nZEB/NZEB (Table 3).…”
Section: Envelope Transmittance Values According To Climatementioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, in Argentina, under the same Cfa climate, the same original U-value was encountered for reaching nZEB [35] for different building types, but to achieve NZEB the improved case presented U-values lower than the original [28] (Table 3). On the other hand, to achieve NZEB, the improved U-values differed significantly in studies based in countries with an Af climate, such as Brazil [39] and Panama [54] (Table 3), despite the same type of building being analyzed (Table 1). An agreement is encountered under the same type of climate, Aw [43,55], for the improved U-values in walls and windows, despite different building types, to achieve nZEB/NZEB (Table 3).…”
Section: Envelope Transmittance Values According To Climatementioning
confidence: 94%
“…This tendency follows the ZEB philosophy, as shown in Figure 7. In fact, it can be observed that NZEB can be reached by applying only passive solutions, regardless of the type of climate (Figure 8a) [35,39,40,42,[45][46][47]51,54,55].…”
Section: Zeb Type and Energy Saving Strategies According To Climatementioning
confidence: 99%
“…In this study, a net-zero energy building is regarded as a building with reduced energy needs [9] and generates more energy than it consumes from renewable energy sources [10]. According to Malaysia's energy statistics, energy consumption per capita has steadily increased throughout the years [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The cooling system of a building is a part of its HVAC system. Examples of various cooling systems are passive cooling (sea breeze) supported by a heat absorption element [75], radiant cooling and underfloor air supply based on absorption chillers and electric chillers, air-soil heat exchanger, and concrete core activation based on a solar absorption chiller [76]. Actually, the HVAC system is the most significant energy consumer in the building [12].…”
Section: Cooling Systemmentioning
confidence: 99%